Jurnal BUSINESS & ENTREPRENEURSHIP: the competitveness of manual and mechanized corn cultivation - Juniska muria sariningpuri, Amzul rifin; rokhani hasbullah (SB-IPB, 2017)
Pada tahun 2015total impor jagung di Indonesia mencapai 3,1 juta ton disebabkan produksi jagung Indonesia yang rendah